The Effect of Vermicompost Fertilizer and Effective Microorganisms (EM4) on The Growth and Yield of Shallots (Allium ascalonicum L) Bima Brebes Cultivars - Nurrizky, Anggif Agistha; Fadilah, Nurul; Maulana, Ibnu; Faqih, Achmad (Devotion : Journal of Research and Community Service, 2023)
This study aims to determine the effect of vermicompost fertilizer dose interaction and effective microorganisms (EM4) on the growth and yield of onion plants (Allium ascalonicum L.) cultivar Bima Brebes. The research was carried out in Karangwangun Village, Babakan District, Cirebon Regency – West Java, from February to May 2023. The design used is an experimental method with a factorial pattern Group Random Design (RAK), consisting of two factors, namely vermicompost fertilizer and effective microorganisms (EM4). Application of vermicompost fertilizer (K), which consists of 3 levels, namely: K1 = 5 tons / ha, K2 = 10 tons / ha, and K3 = 15 tons / ha; Effective Microorganism Factor (EM4) (E) which consists of 3 levels, namely: E1 = EM4 5 cc / Liter of water, E2 = EM4 10 cc / Liter of water, and E3 = EM4 15 cc / Liter of water. Each treatment or experimental unit was repeated three times for a total of 27 plots. Data analysis was carried out using fingerprints and follow-up tests with the Duncan Multiple Distance Test at the level of 5%. The variables observed were plant height (cm), number of leaves per clump (strands), number of saplings per clump (fruit), tuber diameter (cm), weight of fresh tubers per clump, weight of fresh tubers per plot, weight of dry tubers per clump and per plot. The results showed that: (1) there was no interaction between vermicompost fertilizer application and effective microorganisms (EM4) on all observation parameters, (2) The independent effect of vermicompost fertilizer application had a significant effect on the average variable weight of fresh tubers per plot. Meanwhile, the treatment of effective microorganisms (EM4) has an independent effect on the average plant height variable aged 21 days after planting (HST).